Pemanfaatan Metarhizium sebagai Agens Hayati di Kelompok Tani Ngudi Kaweruh, Kabupaten Jember - Siswadi, Edi; Utami, Christa Dyah; Dinata, Gallyndra Fathku; Salim, Abdurrahman; Rohman, Fadil (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The Ngudi Kaweruh Farmer Group is one of the farmer groups in Tegal Rejo Hamlet, Sabrang Village, Ambulu Subdistrict, Jember Regency, which cultivates shallots. The obstacle complained about by this farmer group is the high price of inorganic pesticides in the field. Pesticides do not receive subsidies from the government, while in shallot farming, farmers cannot avoid the use of inorganic pesticides. Based on the problems faced by our partners, we provided an alternative solution, namely the use of Metarhizium as a biological agent to control red onion pests. The program was implemented from February to May 2025. The stages of implementation included surveys and discussions, socialization of the use of Metarhizium, and discussions and assistance. The results of the activity showed that the use of Metarhizium can save farmers' expenses for purchasing inorganic pesticides, control pests, and is environmentally friendly. Farmers can see the real impact of using Metarhizium in shallot cultivation. Therefore, farmers do not hesitate to use Metarhizium to control pests that attack shallots.